Carbon-coated tin nanoparticles, preparation method thereof and lithium ion battery material prepared from carbon-coated tin nanoparticles

By using the Sn@C@CNT and Sn@C/GO anode materials prepared by Bacillus subtilis, the capacity attenuation problem caused by volume expansion of tin-based materials is solved, and high energy density and stable lithium-ion battery performance are achieved.

CN119230799AActive Publication Date: 2024-12-31JIANGXI SCI & TECH NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411646426.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-31
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The capacity of tin-based materials rapidly decay due to volume expansion during the circulation of lithium-ion batteries, affecting their service life and battery performance.

Method used

Bacillus subtilis is used as a biological template to prepare Sn@C@CNT and Sn@C/GO anode materials through biosorbents and renewable carbon sources, and the volume expansion of tin particles is used to alleviate the surface expansion of carbon particles by using the voids in the bacterial carbon shell, and the carbon is compounded on the surface. Nanotubes or graphene oxide to enhance conductivity and stress buffering.

Benefits of technology

Achieved the 70.1% high initial Coulomb efficiency and 721.68 mA h g-¹ reversible capacity of Sn@C@CNT composite material after 150 cycles at 100 mA g-¹ current density, significantly improving the energy density and cycle of lithium-ion batteries stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230799A_ABST
    Figure CN119230799A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated tin nanoparticle, a preparation method thereof and a lithium ion battery material thereof, and relates to the field of battery materials, the preparation method comprises the following steps: dissolving bacillus subtilis spores in deionized water, and adding glucose for activation culture to obtain supernate; adding SnCl4, and incubating to obtain a suspension liquid; adding a complexing agent, carrying out ultrasonic treatment, and centrifuging to remove a complex, so as to obtain centrifugate; centrifugally collecting precipitates; dissolving the precipitate in deionized water, and carrying out ultrasonic oscillation to obtain a solution; the method comprises the following steps: dissolving a carbon nanotube or graphene oxide in a solvent to obtain a carbon nanotube solution or a graphene oxide solution; mixing the solution with the carbon nanotube solution to obtain a mixed solution; freezing and drying; and placing the powder in a protective gas atmosphere for high-temperature annealing to obtain the product. The method has the beneficial effects that voids in the bacterial carbon shell relieve volume expansion of tin particles in lithiation and lithium removal processes, and the carbon nanotubes uniformly integrated in the bacterial carbon shell serve as efficient electron conduction channels to disperse anisotropic stress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to carbon-coated tin nanoparticles, a preparation method thereof, and lithium ion battery materials thereof. Background Art

[0002] As the main energy source for portable electronic devices and electric vehicles, lithium-ion batteries have developed rapidly. However, traditional graphite anodes have difficulty solving the problems of low energy density and short cycle life in electronic devices and electric vehicles, which raises questions about battery capacity. In order to cope with the growing demand for energy and usage, the development of high-energy-density lithium-ion batteries has become an important pursuit for researchers around the world. Traditional graphite anode materials have low energy density, theoretical capacity (372 mA hg - ¹) and slow lithium ion diffusion rate. Therefore, it is particularly important to explore and develop new alternative anode materials to improve energy density.

[0003] Currently, there are many high-capacity anode candidate materials, including materials based on silicon, germanium, tin, sulfides, and various alloys and metal compounds. Although silicon and germanium-based materials have extremely high theoretical capacities, they face the problems of complex synthesis processes and low electrical conductivity. In contrast, tin anode materials have high electrical conductivity and high theoretical capacity (994 mA h g - ¹), has attracted widespread attention from researchers. However, due to the 22 Formation of Sn5, tin anode materials undergo up to 260% volume expansion during charge-discharge cycling. This volume expansion can cause irreversible structural damage during lithium-ion insertion and extraction, allowing the electrolyte to continue to penetrate the damaged structure, thereby reducing its overall performance over time. As a result, the SEI (solid electrolyte interface) film formed on the surface of the material becomes thicker, hindering the transport of lithium ions (thereby reducing ionic conductivity), further leading to a rapid decrease in battery capacity. Therefore, there is an urgent need to address the challenges in the application of tin-based materials.

[0004] To address this issue, researchers have focused on optimizing the morphology, conductivity, and surface chemistry of tin anode materials to improve the performance of lithium-ion batteries. Jaegeon Ryu et al. used a template method to create a flexible 3D graphene-supported tin-based composite with a double-layer coating (TiO2 and SnO2) to enhance electronic conductivity, reduce stress, and improve the stability and performance of lithium-ion battery anodes. Belgigayeva et al. used a one-pot electrospinning technique combined with heat treatment to prepare free-standing tin phosphide / phosphate carbon composite nanofiber mats as an alternative anode material for low-temperature lithium-ion batteries, and studied the material properties and activation mechanism. Xiaoxiao Hou et al. used a novel synthesis method to prepare a low-melting-point dimer bimetallic Sn-Bi@C composite with excellent sodium storage performance, high specific capacity, outstanding cycle stability, and excellent rate performance. Li Rui et al. prepared nitrogen-doped carbon-coated heterostructured Sn / SnO2 microcubic powder (Sn / SnO2@NC) by hydrothermal method, polymerization, and carbonization process. The material exhibits high initial discharge capacity, excellent rate performance and good cycle stability, which can accelerate lithium ion transfer and adapt to volume changes. Xunfu Zhou et al. synthesized SnO2@C@GS composite materials by a simple hydrothermal method and subsequent sintering. This novel 3D nanostructure consists of SnO2@C core-shell nanospheres and nanochains anchored on wrinkled graphene sheets, showing high capacity, excellent cycle stability and rate performance, becoming a promising high-rate and stable anode material in lithium batteries. Compared with the above methods, bio-template technology is an excellent and innovative strategy that can easily endow materials with structural specificity, complexity, and complex functions derived from biomaterials. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. Tin-based materials are considered to be promising anode materials in lithium-ion batteries due to their high theoretical capacity, abundant resources and suitable low discharge potential. However, the main problem they face in practical applications is the rapid capacity decay during the cycle, which is mainly due to pulverization caused by volume change. In order to extend the service life of tin-based anodes, the significant volume strain associated with lithium ion insertion and extraction must be alleviated.

[0006] To this end, the present invention provides a carbon-coated tin nanoparticle, a preparation method thereof, and a lithium-ion battery material thereof, which utilizes the unique biological template characteristics of Bacillus subtilis and uses its bacterial shell as a biological template, a biological adsorbent, and a renewable carbon source. This method successfully prepares submicron-scale Sn@C@CNT and Sn@C / GO anode materials. Nanoscale tin particles are encapsulated in the bacterial carbon shell (0.4 μm wide and 0.9 μm long), and carbon nanotubes (CNTs) or graphene oxide (GO) are compounded on the outside of the bacterial carbon shell. In this design, the voids inside the bacterial carbon shell alleviate the volume expansion of the tin particles during lithiation and delithiation. The carbon nanotubes (CNTs) or graphene oxide (GO) uniformly integrated in the bacterial carbon shell serve as efficient electron conduction channels while dispersing anisotropic stress. This arrangement provides a buffering effect on the mechanical stress generated by volume changes, thereby enhancing structural integrity. In addition, CNTs or GO as Li + The active sites of Sn@C and Sn@C@CNT composites and Sn@C / GO composites have contributed to the increase in the specific capacity of the anode material. The comparative analysis of the electrochemical performance of Sn@C, Sn@C@CNT composites and Sn@C / GO composites shows that the innovative Sn@C@CNT composites and Sn@C / GO composites have excellent lithium storage capacity, high specific capacity, stable cycle performance and excellent rate performance. Specifically, Sn@C@CNT composites have a high specific capacity and stable cycle performance at 100 mA g - ¹After 150 cycles at the same current density, a high initial Coulombic efficiency of 70.1% was achieved and 721.68mA hg - ¹. These findings highlight the great potential of Sn@C@CNT composites as high energy density and stable anode materials. This invention proposes an innovative method to build complex structures by utilizing a simple bio-template approach, thus advancing the application of tin-based materials in energy-related technologies.

[0007] The technical solution of the present invention is as follows: A first aspect of the present invention provides a method for preparing carbon-coated tin nanoparticles, comprising the following steps: S1. Dissolve Bacillus subtilis spores in deionized water, add glucose to activate the culture, centrifuge, and obtain a supernatant; S2, adding SnCl4 to the supernatant of step S1, incubating to obtain a suspension; S3, adding a complexing agent to the suspension of step S2, ultrasonic treatment, and centrifugation to remove the complex to obtain a centrifuge; S4, centrifuging the centrifuge liquid of step S3, collecting the precipitate; dissolving the precipitate in deionized water, and ultrasonically vibrating to obtain a Sn-containing 4+ A solution of Bacillus subtilis; S5, dissolving the carbon nanotubes or graphene oxide in a solvent, and applying ultrasonic vibration to obtain a carbon nanotube solution or a graphene oxide solution; S6, mixing the solution of step S4 with the carbon nanotube solution of step S5, and subjecting the mixture to ultrasonic vibration to obtain a mixed solution; S7, freeze-drying the mixed solution of step S6 to obtain powder; S8, placing the powder of step S7 in a protective gas atmosphere for high temperature annealing to obtain carbon-coated tin nanoparticles.

[0008] Optionally, in step S1, the mass ratio of Bacillus subtilis spores to glucose is 10-12:2-3; the activation culture time is 14-18 hours, the centrifugal speed is 1500-2000 rpm, and the centrifugal time is 1-3 minutes.

[0009] Optionally, in step S2, the addition ratio of Bacillus subtilis spores to SnCl4 is 10-12 g: 2 mL, and the incubation time is 16 to 24 hours.

[0010] Optionally, in step S3, the molar ratio of the complexing agent to SnCl4 is 1-4:1-2, the ultrasonic treatment time is 20-40 minutes, the centrifugal speed is 1600-1700 rpm, and the centrifugal time is 1-3 minutes.

[0011] Optionally, in step S3, the complexing agent is EDTA.

[0012] Optionally, in step S4, the centrifugal speed is 4000-5000 rpm, the centrifugal time is 5-7 minutes, the ultrasonic oscillation frequency is 35-45 KHz, and the ultrasonic oscillation time is 5-7 hours.

[0013] Optionally, in step S5, the amount of carbon nanotubes or graphite oxide added is 1-4% of the mass of the precipitate, the frequency of ultrasonic oscillation is 35-45 KHz, and the time of ultrasonic oscillation is 5-7 hours.

[0014] Optionally, the solvent in step S5 is ethanol.

[0015] In step S6, the frequency of ultrasonic oscillation is 35-45 KHz, and the time of ultrasonic oscillation is 1-3 hours.

[0016] Optionally, in step S7, the freezing time is 3-5 hours, and the drying time is 20-28 hours.

[0017] Optionally, in step S7, the temperature of high temperature annealing is 780-820° C., the heating rate is 8-10° C. / min, and the time is 15-30 minutes.

[0018] The second aspect of the present invention provides carbon-coated tin nanoparticles prepared by the method described above.

[0019] The third aspect of the present invention provides a lithium-ion battery material, comprising the carbon-coated tin nanoparticles.

[0020] The present invention has at least one of the following beneficial effects: The present invention proposes a simple and cost-effective bio-cultivation method to engineer a material in which the tin-based components are encapsulated within bacterial cells and coated with carbon nanofibers (Sn@C / CNT) or graphene oxide (Sn@C / GO) on the surface. The carbon shell on the bacterial surface effectively maintains the structural and interfacial stability of the tin nanoparticles, inhibits their aggregation, and buffers the volume expansion. In addition, the carbon nanofiber network on the surface has high conductivity, large surface area, and excellent mechanical flexibility, which can firmly anchor the core-shell structure of Sn@C. This design significantly enhances the conductivity and structural integrity of the overall electrode. When used as an anode material in lithium-ion batteries, Sn@C / CNT exhibits a high initial coulombic efficiency of 71% and a high charge / discharge rate of 100mA g - ¹After 150 cycles, it has 721.68 mA h g - ¹, and exhibits excellent reversible capacity and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Synthesis flow chart of Sn@C and Sn@C / CNT composites.

[0022] Figure 2 Figure 3 is the morphological structure of Sn@C / CNT. Among them, a, b, c) SEM images of Sn@C / CNT; d, e) TEM images showing the overall structure and local structure respectively; f) TEM image highlighting the surface carbon shell; g, h) local TEM images of tin (Sn) in the carbon shell; i, j, k) elemental maps of tin and carbon. Figure 3 Characterization of Sn@C / CNT. Among them, a) X-ray diffraction (XRD) pattern; b) Raman spectrum; c, d) thermogravimetric analysis (TGA) and differential thermal analysis (DTG); e, f) X-ray photoelectron spectroscopy (XPS) of C1s and Sn3d.

[0023] Figure 4The electrochemical performance of Sn@C and Sn@C / CNT. a) Cyclic voltammograms of Sn@C / CNT in the voltage range of 0.01 to 3.0 V at a scan rate of 2 mV / s for the first five cycles. b, c) Cyclic voltammograms of Sn@C / CNT in the voltage range of 0.01 to 3.0 V at a scan rate of 2 mV / s for the first five cycles. -1 Specific capacities of Sn@C and Sn@C / CNT batteries from the 1st to the 150th cycle at current densities of 100 mA g -1 f) Cyclic performance and Coulombic efficiency of Sn@C and Sn@C / CNT at different current densities (100, 200, 400, 600, 800 and 1000 mA g -1 g) Electrochemical impedance spectroscopy (EIS) of Sn@C / CNT anode material after one cycle and 150 cycles.

[0024] Figure 5 The morphology and structure of Sn@C materials. Among them, a) SEM image of the material synthesized with EDTA (Sn-EDTA molar ratio is 1:1); b) SEM image of the material synthesized with EDTA (Sn-EDTA molar ratio is 2:1); c) SEM image of the material synthesized with EDTA (Sn-EDTA molar ratio is 1:2); d) SEM image of the material synthesized with EDTA (Sn-EDTA molar ratio is 1:4); e) XRD patterns of materials with different Sn and EDTA molar ratios (1:1, 2:1, 1:2, 1:4).

[0025] Figure 6 This is the scanning electron microscope image of Sn@C material without EDTA.

[0026] Figure 7 The morphology and structure of Sn@C and Sn@C / CNT, where a, b) high-resolution TEM (transmission electron microscopy) images and SAEM (selected area electron microscopy) images show lattice fringes. c) High-resolution SEM (scanning electron microscopy) images of bacterial fracture in Sn@C.

[0027] Figure 8 This is the EDX spectrum of Sn@C / CNT.

[0028] Fig. 9Scanning electron microscope images of Sn@C / CNT with different proportions of carbon nanotubes, where (a, b) are SEM (scanning electron microscope) images of Sn@C / CNT materials containing different proportions of carbon nanotubes (1%, 2%, 3%, 4%).

[0029] Fig.10 XRD patterns of Sn@C / CNT at different CNT contents (1%, 2%, 3%, 4%).

[0030] Fig.11 SEM images of Sn@C / GO with different CNT contents (1%, 2%, 3%, 4%); a) Scanning electron microscopy (SEM) of Sn@C / GO materials containing different proportions of graphene oxide (1%, 2%, 3%, 4%).

[0031] Fig.12 The effect of adding different ratios of carbon nanotubes (CNTs) and graphene oxide (GO) on the cycling stability of the battery. Among them, a) different CNT contents (initial, 1%, 2%, 3%, 4%) of materials at 100 mA g -1 Electrochemical performance under current density; b) Electrochemical performance of materials with different GO contents (1%, 2%, 3%, 4%) at 100 mA g -1 Electrochemical performance at different current densities.

[0032] Fig.13 At 500 mA g -1 Nyquist plot equivalent circuit model after 200 cycles under the same conditions.

[0033] Fig.14 SEM images of the electrodes. (a) Sn@C / CNT-1% before cycling; (b) Sn@C / CNT-1% after cycling, showing structural changes; (c) Sn@C / GO-2% before cycling; (d) Sn@C / GO-2% after cycling, highlighting morphological differences. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0036] Sources of the raw materials in the following examples: Bacillus subtilis (provided by Hebei Longyang Biotechnology Co., Ltd., China), glucose (C6H 12 O6·H2O, Aladdin Biochemical Technology Co., Ltd., China), deionized water (homemade), EDTA (ethylenediaminetetraacetic acid, Xilong Scientific Co., Ltd., China), SnCl4 (tin tetrachloride, MacLean Biochemical Technology Co., Ltd., China), and carbon nanotubes (CNTs, Jiangsu Xianfeng Nanomaterials Co., Ltd., China).

[0037] Comparative Example 1 This comparative example provides a method for synthesizing Sn@C, comprising the following steps: 10 g of Bacillus subtilis spores were dissolved in 250 ml of deionized water, and 2 g of glucose was added and placed in a petri dish. After activation and culturing for 16 hours, a mixed solution of Bacillus subtilis and glucose was obtained. To isolate pure and active Bacillus subtilis, the mixture was centrifuged at 1500 rpm for 2 minutes, the supernatant was poured into a clean petri dish, and the precipitate was discarded. 2 ml of SnCl4 solution was added to the petri dish containing the supernatant, stirred well and incubated for 24 hours to obtain a suspension containing SnCl4 and Bacillus subtilis. Different proportions of EDTA (the molar ratio of EDTA to the added SnCl4 was 1:2, 2:1, 4:1 and 1:1, respectively) were added to the suspension, ultrasonically treated for 30 minutes, and then centrifuged at 1600 rpm for 2 minutes to remove the surface chelate. Then a solution containing Bacillus subtilis adsorbed with Sn ions was obtained. Finally, the solution was centrifuged at 4500 rpm for 7 min, the precipitate was collected, resuspended in ethanol, and centrifuged at 4500 rpm for 5 min to collect the final precipitate. After freeze-drying the precipitate for 24 h, it was annealed at 800 °C for 30 min in a tube furnace under argon atmosphere to obtain [Sn@C].

[0038] The overall synthesis process of Sn@C is as follows Figure 1 As shown. The process includes two main strategies. First, Bacillus subtilis (BS) adsorbs metal salts (SnCl4). In this step, the bacteria are cultured in deionized water containing glucose for 16 h to obtain a bacterial precursor solution. In our experiments, when excess SnCl4 (2 mL added to 200 mL deionized water) was introduced into the BS solution after 16 h of culture at room temperature, the bacteria died or entered a dormant state. The bacteria adsorbed Sn through their cell walls. 4+ ions and retained internally. Next, Sn was adsorbed by centrifugation at different speeds. 4+ ions of bacteria and add them to EDTA solution to remove Sn on the surface 4+Finally, the annealing was performed in an argon-filled tube furnace at a heating rate of 7°C per minute to 800°C and maintained for 30 minutes. During the annealing process, the bacterial cell wall was converted into carbon, and the high-temperature annealing reduction process reduced the adsorbed Sn 4+ The ions are converted to elemental Sn.

[0039] Figure 6 The SEM images in Figure 2 show that without EDTA, there is a thick adhesion layer and a large number of aggregated Sn balls on the surface of the Sn@C material. Figure 5 As shown in (bd), the surface of the bacterial template becomes cleaner and cleaner, and the size of the Sn spheres decreases. Figure 6 It can be observed that the diameter of the solder balls is about 1.2 microns. Figure 5 (ad) show SEM images of Sn:EDTA ratios of 1:1, 2:1, 1:2, and 1:4, respectively. Figure 5 b, we can see that the diameter of the solder ball has been reduced to 0.6 microns. Figure 5 c shows a reduction in the number of solder balls. Figure 5 As shown in d, only a small amount of Sn particles remain on the surface, while Figure 5 These tin balls or tin particles in a almost completely disappeared, indicating that the surface Sn 4+ It can be removed by complexation using EDTA. XRD analysis ( Figure 5 e) shows that as the EDTA content increases, the intensity of the XRD peak gradually decreases, but it has little effect on the appearance of the Sn peak. It can be determined that the 1:1 ratio of Sn to EDTA is the optimal ratio for removing surface Sn. 4+ After the bacteria are exposed to Sn, a large amount of Sn is still retained inside the bacteria. This phenomenon is attributed to the bacteria's 4+ The adsorption of the complexing agent and the internal Sn 4+ reaction.

[0040] Example 1 This embodiment provides a method for synthesizing carbon-coated tin nanoparticles (Sn@C / CNT), comprising the following steps: 10 g of Bacillus subtilis spores were dissolved in 250 ml of deionized water, and 2 g of glucose was added and placed in a petri dish. After activation and culturing for 16 hours, a mixed solution of Bacillus subtilis and glucose was obtained. To isolate pure and active Bacillus subtilis, the mixture was centrifuged at 1500 rpm for 2 minutes, the supernatant was poured into a clean petri dish, and the precipitate was discarded. 2 ml of SnCl4 solution was added to the petri dish containing the supernatant, stirred thoroughly and incubated for 24 hours to obtain a suspension containing SnCl4 and Bacillus subtilis. Different proportions of EDTA (the molar ratio of EDTA to the added SnCl4 was 1:2, 2:1, 4:1 and 1:1, respectively) were added to the suspension, ultrasonically treated for 30 minutes, and then centrifuged at 1600 rpm for 2 minutes to remove the surface chelate. Then a solution containing Bacillus subtilis adsorbed with Sn ions was obtained. Finally, the solution was centrifuged at 4500 rpm for 7 minutes and the precipitate was collected.

[0041] The obtained lower precipitate was dissolved in a beaker containing 25 ml of deionized water. 25 ml of ethanol was added to another beaker, and 1%, 2%, 3%, and 4% (1%, 2%, 3%, and 4% of the mass of the lower precipitate) of carbon nanotubes (CNT) were added respectively. The two beakers were placed in an ultrasonic oscillator, set to a frequency of 40 KHz, and oscillated for 6 hours. The solutions in the two beakers were then combined into one beaker and continued to oscillate for 2 hours under the same conditions. Subsequently, the resulting solution was placed in a freeze dryer, frozen for 4 hours, and dried for 24 hours. Finally, the obtained powder was transferred to a tube furnace for high-temperature annealing under an argon atmosphere, with the temperature rising at a rate of 9°C per minute to 800°C for 30 minutes to obtain [Sn@C / CNT].

[0042] In order to enhance the conductivity of the material, Figure 1 The method shown in the figure adds a small amount of carbon nanotubes on the basis of comparative example 1. 4+ Then, carbon nanotubes were introduced in a specific ratio. After being fully mixed, the mixture was placed in a tube furnace filled with argon and annealed at 800°C for 30 minutes at a heating rate of 9°C per minute.

[0043] Figure 2 (ac) show the surface morphology of C-coated Sn nanostructures synthesized by bio-template method, observed by SEM. Figure 2 In c, the SEM image shows a rod-shaped bacterial structure with dimensions of approximately 0.8 µm long and 0.4 µm wide, covered with carbon nanotubes ( Figure 2 b), which results in closer contact between bacteria. TEM image ( Figure 2 e) also clearly shows this rod-shaped morphology, Figure 2f shows that there is an obvious boundary layer with a thickness of 6 nm on the surface, which is the result of carbonization of the bacterial shell during annealing.

[0044] In order to further confirm the Sn 4+ Whether it has been completely removed, it is necessary to verify Sn 4+ Whether it has been internally absorbed. The clear crystalline phase of Sn is highlighted in the high-resolution TEM images. According to these HR-TEM images ( Figure 7 a) The calculated d-spacing of the lattice fringes is 0.29 nm. Selected area electron diffraction (SAED) pattern ( Figure 7 b) shows diffraction rings consistent with the single crystal structure of Sn. TEM image ( Figure 2 g) reveals that the internal structure is composed of bulk Sn. Figure 2 h, the measured sizes of bulk Sn along three different axes are 36.08 nm, 68.25 nm, and 102.61 nm, respectively, indicating that Sn is retained inside the bacteria in the form of nanoparticles and has not aggregated into Sn balls. Figure 7 c), this conclusion is further supported. In addition, the element mapping image ( Figure 2 i, j, k) show that Sn and C are evenly distributed inside the bacteria. These results indicate that Sn@C / CNT has an excellent morphological structure.

[0045] To further confirm the structural characteristics of the material, XRD analysis showed obvious diffraction peaks at 2θ of 30.644°, 32.018°, and 43.871°, corresponding to the (200), (101), and (221) crystal planes, respectively. Figure 3 a). These diffraction peaks indicate that the Sn nanostructures have good crystallinity and present a tetragonal crystal structure. The lattice parameters calculated from the XRD data are a = 5.832 nm, c = 3.181 nm. It is worth noting that no secondary peaks related to impurities or other phases of Sn were observed, indicating that the chelation method is very effective in removing excess Sn from the surface, thereby avoiding the introduction of other impurities.

[0046] In Raman spectroscopy ( Figure 3 b), 1335 cm - ¹ and 1581 cm - The two main peaks at ¹ correspond to the D band and the G band, respectively. The D band represents defects in amorphous carbon, while the G band is characteristic of graphitic carbon. The ID / IG ratio exceeds 0.99, reflecting the presence of a large number of microstructural defects in the carbon shell, indicating that there are many defects and vacancies in the carbon shell, and also a certain degree of graphitization. This coexistence of graphitization, defects, and vacancies not only accelerates the Li + transmission, but also for Li +Storage provides numerous active sites.

[0047] TGA Figure 3 c) and DTG ( Figure 3 d) The component contents of the materials were quantified in air. Below 300°C, the weight loss curve showed a loss of approximately 7.41%, mainly due to water evaporation and slight reactions of reduced phosphorus (P) and sulfur (S) inside the bacteria with oxygen. The mass loss between 400°C and 600°C was approximately 40.7%, attributed to the reaction of surface carbon (C) with air to produce CO2. At approximately 566°C, the TGA curve showed a significant decrease in slope and a local minimum in the DTG curve, indicating that Sn reacted with air to produce SnO2, resulting in an increase in mass. Despite this, the overall trend of the TGA curve was downward, and the final mass remained at 51.9%. Figure 3 It can be analyzed that there are trace amounts of other metal elements (such as Ca, Mg, and Al) inside pure bacteria. In order to better analyze the Sn content, the Sn@C / CNT material was dissolved and diluted 10,000 times, and the Sn content was measured to be 16.96%, as shown in Table 1.

[0048] Table 1 X-ray photoelectron spectroscopy (XPS) was used to study the chemical composition and bonding state of the Sn@C / CNT electrode, confirming the presence of C and Sn. Figure 3 As shown in e and f, the high-resolution spectra of C 1s and Sn 3d were analyzed. Figure 3 e), the three fitted peaks at 284.8 eV, 285.7 eV, and 286.8 eV correspond to C=C, CO, and C=O bonds, respectively. Figure 3 f), the two peaks at 495.8 eV and 486.3 eV are attributed to Sn, respectively. 0 3d 5 / 2 and 3D 3 / 2 The peaks at 487.3 eV and 498.5 eV correspond to Sn 4+ 3d 5 / 2 and 3D 3 / 2 , while the peak at 496.8 eV is attributed to Sn-O, indicating the presence of oxidized Sn on the surface. Figure 8 Figure 2 is the EDX spectrum of Sn@C / CNT. The elements present in the material were analyzed using energy dispersive X-ray spectroscopy (EDX). The main non-metallic elements identified were C, O, P, and S, while the metallic elements included Ca, Mg, Al, Sn, and Na. Figure 8 It was also shown that the presence of small amounts of oxygen in the bacteria led to the formation of trace amounts of SnO2.

[0049] Example 2 This embodiment provides a method for synthesizing carbon-coated tin nanoparticles (Sn@C / GO). The preparation method is the same as that of Example 1, except that the carbon nanotubes in Example 1 are replaced with graphene oxide, and the other steps are the same as those of Example 1.

[0050] Wherein, the preparation method of graphene oxide is prepared according to the Hummers method.

[0051] Example 3 The Sn@C synthesized in Comparative Example 1, the Sn@C / CNT synthesized in Example 1, and the Sn@C / GO synthesized in Example 2 were used as lithium-ion battery materials and applied in lithium-ion batteries to test the electrochemical properties of Sn@C, Sn@C / CNT, and Sn@C / GO.

[0052] The electrochemical performances of Sn@C, Sn@C / CNT, and Sn@C / GO were evaluated using lithium metal button cells as the counter electrode as follows: Electrochemical performance tests were performed using CR2032 button cells. The working electrode was prepared by mixing the active material, acetylene black and polyvinylidene fluoride (PVDF) in N-methyl-2-pyrrolidone (NMP) at a mass ratio of 80:10:10 to form a uniform slurry, which was coated on a copper foil substrate and then dried overnight in a vacuum oven at 55°C. The battery was assembled in a glove box filled with high-purity argon, using pure lithium sheets as counter and reference electrodes, Celgard 2400 membrane as a separator, and 1.0M LiPF6 dissolved in a mixed solvent of EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate) in a volume ratio of 1:1:1 as the electrolyte.

[0053] Figure 4a shows representative cyclic voltammograms (CVs) of the first five cycles in the voltage range of 0.01 to 3.0 V at a scan rate of 2 mV / s. Electrochemical kinetic analysis showed that the first discharge cycle showed two subtle peaks at 0.83 V and 1.19 V, while the first charge cycle showed two similar but less obvious peaks at 0.76 V and 1.41 V, respectively. These peaks became more prominent in subsequent cycles. In the second charge-discharge cycle, two obvious peaks at 0.83 V and 1.41 V were observed, which were attributed to the reversible reaction between the surface carbon layer and lithium ions (Equation 1). The peaks at 1.19 V and 0.76 V are related to the reversible alloying reaction between Sn and lithium ions (Equation 2). With the increase in the number of cycles, these peaks gradually stabilized, indicating that the Sn@C / CNT structure has good stability and excellent electrochemical reversibility.

[0054] Figure 4b and Figure 4c show the Sn@C and Sn@C / CNT-1% at a current density of 100 mA g -1 The charge-discharge curves for the 1st, 10th, 50th, 100th and 150th cycles under the same conditions are shown in Figure 4b. In Figure 4b, the voltage platform observed in the range of 0-1.3 V during the first discharge process is related to the formation of the SEI film and the insertion of lithium ions into the negative electrode material, achieving 573.1 and 848.5 mA h g -1 The initial charge-discharge capacity of the battery is 1156.1 mA h g. -1 , indicating that Sn@C / CNT-1% has a higher discharge capacity than Sn@C. This enhancement is mainly attributed to the addition of CNTs, which increases the active sites of the material, improves the conductivity, and accelerates the transfer rate of lithium ions. The charge-discharge capacity curves from the 10th to the 150th cycle show stability, indicating that Sn encapsulated in the carbon material effectively improves the electrochemical stability of the battery. After 150 charge-discharge cycles, Sn@C maintained a charge capacity of 534.45 mA h g -1 The reversible capacity of Sn@C / CNT-1% was 721.6 mA h g -1The reversible capacity of Sn@C / CNT-1% is 62.4% (capacity retention rate). Compared with Sn@C, Sn@C / CNT-1% shows higher initial and reversible capacity, where the presence of CNTs slows down the volume expansion of Sn to a certain extent, thereby maintaining the structural stability of the material and improving the electrochemical reversibility of the battery.

[0055] The cycling performance of the electrode is in the voltage range of 0.01−3.0 V and 100 mA g -1 The charge and discharge specific capacities of Sn@C / CNT-1% were 803.44 and 1156.16 mA h g in the first cycle, respectively. -1 , while the capacities of Sn@C are 573.16 and 848.58 mA h g -1 . The observed large capacity irreversibility may be attributed to the consumption of electrolyte solution during the formation of SEI film. Figure 4e shows that the first coulombic efficiency (ICE) of Sn@C / CNT-1% is about 70.1%, while that of Sn@C is about 67.5%. However, after the second cycle, the coulombic efficiency increases rapidly to 99%. This result is consistent with numerous studies showing that the first coulombic efficiency is affected by the large amount of lithium ions consumed during the formation of SEI film on the electrode surface. This indicates that a stable SEI film is formed on the surface of the anode material, which contributes to the stable cycling performance. Compared with Sn@C, Sn@C / CNT-1% not only exhibits higher initial capacity and first coulombic efficiency, but also shows significantly improved reversible capacity after 150 cycles, reflecting superior electrochemical stability. This enhancement is attributed to the addition of CNTs, which increases the active sites of the material, improves the conductivity, accelerates the lithium ion transport rate, and partially slows down the volume expansion of Sn.

[0056] Figure 4 f shows the performance of Sn@C / CNT-1% and Sn@C at different current densities. For Sn@C / CNT-1%, the performance of Sn@C / CNT-1% at different current densities (100, 200, 400, 600, 800 and 1000 mA g -1 ) are approximately 705.54, 543.66, 443.25, 392.24, 366.70, and 362.72 mA h g -1 When the current density returns to 100 mAg -1 When the battery charge and discharge capacity is restored to 606.53 mA h g -1For Sn@C, the reversible capacities at the same current density are approximately 436.89, 326.65, 250.52, 212.66, 199.10, and 192.23 mA h g -1 . Restore to 100mA g -1 When the charge-discharge specific capacity of Sn@C is restored to 322.53 mA h g -1 . Figure 4 g shows the Nyquist plot of Sn@C / CNT before and after 150 cycles, obtained by electrochemical impedance spectroscopy (EIS) with a frequency range of 100 kHz to 0.01 Hz and an amplitude of 10 mV. Fitting using the equivalent circuit model Fig.13 The electrochemical impedance spectroscopy (EIS) data of the battery in the figure shows two main impedance components: Rs (ohmic resistance) and Rct (charge transfer resistance). Table 2 shows that after one cycle, the resistances of Rs and Rct are 171.3 Ω and 938.4 Ω, respectively. After 150 cycles, Rs and Rct dropped significantly to 19.49 Ω and 138.1 Ω. This shows that during the cycle process, the battery exhibits good ionic conductivity and forms a stable solid electrolyte interface (SEI) layer. The stability of the impedance component contributes to the excellent cycling performance of the Sn@C / CNT battery.

[0057] Table 2 Sn@C / CNT as lithium-ion battery anode at 500 mA g - 1 Nyquist plot fitting results after 200 cycles This example also studies the effect of adding different proportions of carbon nanotubes (CNTs) on the battery cycle stability. Materials with different CNT proportions were prepared, and their morphology and structure were observed and their characteristics were analyzed using XRD and SEM. Fig. 9 As shown in (ad), SEM images of materials with different CNT ratios (1%, 2%, 3%, and 4%) can be observed. As the CNT ratio increases, the carbon nanotubes gradually aggregate into larger block structures. Fig.10 The XRD peaks of different CNT ratios correspond to the standard Sn card, confirming that Sn is still the main component of the material. We also prepared button batteries and tested them at a current density of 100 mAg −1 The cycling performance of the electrode was tested under the conditions of 0.01-3 V. Fig.12As shown in a, the initial Coulombic efficiencies of different CNT ratios (1%, 2%, 3%, 4%, 0%) are 70.1%, 34.6%, 41.2%, 79.9%, and 67.0%, respectively. After multiple cycles, the Coulombic efficiency stabilizes at about 99%. After 150 cycles, the reversible capacities of different CNT ratios (1%, 2%, 3%, 4%, 0%) are 721.68, 420.37, 335.80, 380.23, and 463.34 mA h g −1 The results showed that 1% CNT addition ratio was optimal because it not only increased the initial Coulombic efficiency but also improved the cycle stability of the negative electrode material.

[0058] This example also studies the effect of graphene oxide (GO) on the material. By preparing materials with different GO ratios and observing their morphology using SEM, we gain insights into the effect of GO addition. Fig.11 As shown in the figure, SEM images of materials with different GO ratios (1%, 2%, 3%, and 4%) can be seen. As the GO ratio increases, GO covers the surface of the material to form a "sandwich" structure. We prepared a button battery and tested it at a current density of 100 mA g −1 The cycling performance of the electrode was tested under the conditions of 0.01-3 V. Fig.12 b shows that the initial Coulombic efficiencies of different GO ratios (1%, 2%, 3%, 4%) are 51.1%, 52.1%, 58.8% and 65.8%, respectively. After many cycles, the Coulombic efficiency stabilized at about 99%. After 150-200 cycles, the reversible capacities of different GO ratios (1%, 2%, 3%, 4%) were 473.74, 611.23, 536.98 and 283.67 mA h g-1, respectively. The results show that the material with 2% GO added exhibits the best cycling performance. In summary, adding GO to Sn@C / GO materials can improve the Coulombic efficiency and reversible specific capacity. However, compared with Sn@C / GO, Sn@C / CNT materials perform better in charge and discharge specific capacity and cycle stability. As Fig.12 As shown in Figure 2, the specific capacities of the samples with 1% CNT and 2% GO after 150 cycles were 721.68 mA h g -1 and 611.23 mA hg -1 In addition, the cycling curve of 1% CNT is significantly more stable than that of 2% GO, confirming that the addition of 1% CNT is the best ratio to improve the performance of the material. As shown in Table 1, compared with other materials, this material has the characteristics of simple preparation method and excellent electrochemical performance.

[0059] In order to better understand the role of carbon nanotubes and graphene oxide in improving the electrochemical performance of Sn@C / CNT-1% and Sn@C / GO-2% composites, we used scanning electron microscopy to analyze the morphological changes of the electrodes before and after cycling, such as Fig.14 shown. Fig.14 a and Fig.14 b shows the SEM images of the Sn@C / CNT-1% electrode before and after the cycle. Fig.14 In a, the carbon nanotubes are clearly visible and evenly distributed within the material, which facilitates internal connectivity and improves electrical conductivity, thereby increasing the utilization of active materials and improving electrochemical performance. Fig.14 As shown in (b), the boundaries between carbon nanotubes are no longer clear, the active materials have agglomerated, and there is a significant volume expansion. However, no obvious structural fragmentation is observed, and the integrity of the overall structure is maintained. Fig.14 c and Fig.14 d shows the SEM images of the Sn@C / GO-2% electrode before and after cycling. Fig.14 In c, we can see the graphene oxide structure covering the surface of the bacteria. After the cycle, Fig.14 d shows that the structure of graphene oxide is partially destroyed, forming a smaller layered structure that is evenly distributed on the surface of the material. This also explains the Fig.12 b Capacity recovery phenomenon observed. However, the capacity of the GO-based material is lower than that of the CNT-based material, which may be due to the uneven initial distribution of GO around the Sn particles, resulting in reduced conductivity and less efficient utilization of the active material. Therefore, the electrochemical performance of the GO composite is not as good as that of the CNT composite at the beginning of the cycle.

[0060] In summary, the present invention adopts a simple bio-template method to synthesize Sn@C / GO nanostructures and a maximum reversible capacity of 721.68 mA h g - ¹ Sn@C / CNT nanostructures. Half-cell studies of the synthesized Sn@C / CNT- and Sn@C / GO structures show that superior performance materials can be obtained by adding CNT or GO to Sn@C. The bacterial-derived carbon shell significantly mitigates the volume expansion of Sn, while the surface carbon nanotubes or graphene oxide enhance the conductivity and ion transport efficiency, thereby accelerating the reaction kinetics. This invention proposes a novel and highly feasible method to design negative electrode materials with high reversible capacity and excellent stability.

[0061] This invention is supported by the Natural Science Foundation of Jiangxi Province (No.20202BABL204049).

[0062] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing carbon-coated tin nanoparticles, characterized in that: The following steps are involved: S1. Dissolve Bacillus subtilis spores in deionized water, add glucose to activate the culture, centrifuge, and obtain a supernatant; S2, adding SnCl4 to the supernatant of step S1, incubating to obtain a suspension; S3, adding a complexing agent to the suspension of step S2, ultrasonic treatment, and centrifugation to remove the complex to obtain a centrifuge; S4, centrifuging the centrifuge liquid of step S3, collecting the precipitate; dissolving the precipitate in deionized water, and ultrasonically vibrating to obtain a Sn-containing 4+ A solution of Bacillus subtilis; S5, dissolving the carbon nanotubes or graphene oxide in a solvent, and applying ultrasonic vibration to obtain a carbon nanotube solution or a graphene oxide solution; S6, mixing the solution of step S4 with the carbon nanotube solution or graphene oxide solution of step S5, and subjecting to ultrasonic oscillation to obtain a mixed solution; S7, freeze-drying the mixed solution of step S6 to obtain powder; S8, placing the powder of step S7 in a protective gas atmosphere for high temperature annealing to obtain carbon-coated tin nanoparticles.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of Bacillus subtilis spores to glucose is 10-12:2-3; the activation culture time is 14-18 hours, the centrifugal speed is 1500-2000 rpm, and the centrifugal time is 1-3 minutes.

3. The preparation method according to claim 1, characterized in that: In step S2, the addition ratio of Bacillus subtilis spores to SnCl4 is 10-12 g: 2 mL, and the incubation time is 16 to 24 hours.

4. The preparation method according to claim 1, characterized in that: In step S3, the molar ratio of the complexing agent to SnCl4 is 1-4:1-2, the ultrasonic treatment time is 20-40 minutes, the centrifugal speed is 1600-1700 rpm, and the centrifugal time is 1-3 minutes.

5. The preparation method according to claim 1, characterized in that: In step S4, the centrifugal speed is 4000-5000 rpm, the centrifugal time is 5-7 minutes, the ultrasonic oscillation frequency is 35-45KHz, and the ultrasonic oscillation time is 5-7 hours.

6. The preparation method according to claim 1, characterized in that: In step S5, the amount of carbon nanotubes or graphite oxide added is 1-4% of the mass of the precipitate, the frequency of ultrasonic oscillation is 35-45 KHz, and the time of ultrasonic oscillation is 5-7 hours. In step S6, the frequency of ultrasonic oscillation is 35-45 KHz, and the time of ultrasonic oscillation is 1-3 hours.

7. The preparation method according to claim 1, characterized in that: In step S7, the freezing time is 3-5 hours, and the drying time is 20-28 hours.

8. The preparation method according to claim 1, characterized in that: In step S7, the high temperature annealing temperature is 780-820°C, the heating rate is 8-10°C / min, and the time is 15-30 minutes.

9. Carbon-coated tin nanoparticles prepared by the method according to any one of claims 1 to 8.

10. A lithium ion battery material, characterized in that: The invention comprises the carbon-coated tin nanoparticles as claimed in claim 9.

Citation Information

Patent Citations

  • Method for preparing positive electrode material of lithium-sulfur battery based on bacterial cellulose

    CN110808361A

  • Preparation method of SnO2@Sn coated reduced graphene oxide composite material

    US11688850B1

  • Carbon nanotube based microbial fuel cells and methods for generating an electric current

    US20180145364A1